Tutorial aplikasi google sites untuk merancang pembelajaran IPA di SD - Fika Anjani Putri (ARKA INSTITUTE, 2022)
This research is motivated by the current pandemic conditions that require students to study from home. There are several factors that make students less attractive to study, namely the lack of interest in learning and learning materials that do not attract interest in learning. The research method used is quantitative. The technique used to collect data is in the form of a literature study used by researchers to explain tutorials from the Google Sites application. The data is the steps from the Google Sites application that will be used to design science learning.